ZnO nanoparticles induce acute arrhythmia and heart failure in mice by disturbing cardiac ion channels - Liu, Xuexue; Deng, Hongmei; Zhao, Zijuan; Wen, Shan; Ma, Kailong; Wang, Xinyu; Du, Yanfei; Li, Chang; Li, Jun; Zhang, Guangqin; Zhou, Xiaobo; Soong, Tuck Wah; et al. (Frontiers in Cardiovascular Medicine, 2025)
BackgroundThe widespread use of zinc oxide nanoparticles (ZnO NPs) has raised safety concerns on human health. However, the effects and underlying mechanisms of ZnO NPs exposure on the heart, especially during acute exposure, have yet to be elucidated.MethodsTwo different sizes of ZnO NPs (40 nm and 100 nm) were selected and their in vivo effects on mouse heart were evaluated by echocardiography and electrocardiograms. Action potential, ion channel currents, and calcium recordings were employed to assess the electrical alterations in individual myocytes. The underlying mechanisms were further investigated by transmission electron microscopy (TEM) imaging, mitochondrial staining, LDH and ROS detection. In addition, human-induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CMs) were utilized for translational exploration.ResultsAcute exposure to ZnO NPs induces cardiac dysfunction and arrhythmia in mice. Mechanistically, exposure to ZnO NPs did not significantly affect the IK1, but it markedly decreased INa and ICa−L currents, resulting in a reduced amplitude and shortened duration of the action potential in cardiomyocytes. These changes not only prolonged PR-interval and blocked A-V conduction that triggered cardiac arrhythmia, but also led to a diminished calcium transient, which contributed to heart failure. The downregulation of calcium transient upon ZnO NPs exposure was further confirmed in hiPSC-CMs. Meanwhile, acute exposure to ZnO NPs did not induce endocytosis, impair membrane integrity, or promote ROS production in the mitochondria of cardiomyocytes.ConclusionAcute ZnO NPs exposure causes heart failure and arrhythmia in mice by directly impacting ion channel function.